Harmonisasi Hukum Konstitusi dan Hukum Islam dalam Perlindungan Warisan Budaya Papua di Tengah Pembangunan Infrastruktur: Studi Kasus Situs Batu Peradaban Aitumeiri - Enny Martha Sasea; Marwati Riza; Syamsul Bachri; Ahmad Masum; Maskun Maskun (Syariah: Jurnal Hukum dan Pemikiran, 2025)
Rapid infrastructure development in Papua has intensified tension between economic growth and the protection of indigenous cultural heritage. This condition represents a critical phenomenon marked by regulatory change and the urgent need for sustainable legal solutions in culturally sensitive regions. Existing legal frameworks often operate in a fragmented manner, weakening effective heritage protection. The theoretical framework of this study lies at the intersection of constitutional law, Islamic law, and legal pluralism. Although the Indonesian Constitution guarantees cultural advancement and the recognition of indigenous rights, and Islamic law provides ethical guidance through maqāṣid al-sharīʿah, their integration in heritage governance remains limited. This study aims to examine the harmonization of constitutional law and Islamic law in protecting Papua’s cultural heritage, using the Aitumeiri Civilization Stone Site as a case study. The research employs a normative legal method with statutory and conceptual approaches, supported by qualitative analysis and a maqāṣid al-sharīʿah framework focusing on the protection of religion, intellect, and lineage. The findings reveal overlapping regulations, weak intergovernmental coordination, and limited indigenous participation as major obstacles to effective heritage governance. Integrating maqāṣid al-sharīʿah into constitutional interpretation strengthens normative coherence and moral legitimacy. In conclusion, harmonized and inclusive legal frameworks are essential to safeguard Papua’s cultural heritage within sustainable development. The study recommends strengthening maqāṣid-based regional regulations, institutionalizing consultative mechanisms inspired by shūrā, and mandating heritage impact assessments involving indigenous communities.